Music & peace values in action engaging students in the music appreciation course - Manrique, Juliana Moonette S. (The Scholastican Journal, 2011)
The purpose of this action research was to use songwriting in the Music Appreciation course as a tool for understanding and communicating peace values. The study investigated the impact of songwriting on the college students' awareness and praxis towards social responsibility and peace building. As an action research, a transformative music pedagogy was designed and field-tested for 8 weeks among 139 college students in the Music Appreciation course at St. Scholastica's College-Manila. The research data generated from the projects and questionnaires that were given to the students were analyzed qualitatively. While the study does not negate the possibility of music as a source of conflict and peacelessness, a significant finding of the investigation pointed out how music could be a potent social force in education towards a culture of justice and peace.